2015
DOI: 10.1016/j.ijresmar.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Recommended for you: The effect of word of mouth on sales concentration

Abstract: I examine the role of word of mouth in consumer's product discovery process and its implications for the firm. A monopolist supplies an assortment of horizontally differentiated products and consumers search for a product that matches their taste by sampling products from the assortment or by seeking product recommendations from other consumers. I analyze the underlying consumer interactions that lead to the emergence of word of mouth, examine the optimal pricing and assortment strategy of the firm, and explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…We consider the situation where one customer (the first person) is satisfied with the product he has purchased and passes on this information to another customer (the second person). It is most likely that the second person will choose to buy the same product as a result of the word-of-mouth effect (Ajorlou et al, 2016;Hervas-Drane, 2015;Peluso et al, 2017). In this case, we assume that the recycling and remanufacturing efforts of enterprises increase customers' environmental awareness and stimulate customers to buy more remanufactured products.…”
Section: Customer's Environmental Awareness and The Word-of-mouth Effectmentioning
confidence: 99%
“…We consider the situation where one customer (the first person) is satisfied with the product he has purchased and passes on this information to another customer (the second person). It is most likely that the second person will choose to buy the same product as a result of the word-of-mouth effect (Ajorlou et al, 2016;Hervas-Drane, 2015;Peluso et al, 2017). In this case, we assume that the recycling and remanufacturing efforts of enterprises increase customers' environmental awareness and stimulate customers to buy more remanufactured products.…”
Section: Customer's Environmental Awareness and The Word-of-mouth Effectmentioning
confidence: 99%
“…Recent evidence suggests that online reviews have become increasingly important in consumer decisionmaking and consequently have an effect on the sale of products and services (Decker & Trusov, 2010;Ghasemaghaei & Hassanein, 2015;Hervas-Drane, 2015;Ho-Dac, Carson, & Moore, 2013;Zhu & Zhang, 2010). As the information contained in online consumer reviews does not originate from producers, consumers usually consider such user-generated content more credible and influential than that generated by producers (Bickart & Schindler, 2001;Winer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The crucial role of review valence has been demonstrated in that only when reviews are perceived as positive does information regarding utility affect product attitude and purchase intention. Second, unlike many prior studies on electronic word of mouth that have analyzed the effects of user-generated product reviews either from the retailers' perspective (e.g., product sales) (e.g., Decker & Trusov, 2010;Hervas-Drane, 2015;Zhu & Zhang, 2010) or from consumers' perspective (e.g., product choice or purchase intention; Senecal & Nantel, 2004), our study is among the first to examine the effects from both sides. From this angle, our findings offer a much more complete picture for policy makers, consumers, and online retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Findings provided by [22] show substantial differences in the effectiveness of received WOM across countries. By analogy to the fact that word of mouth (WOM) is fundamental to the product discovery process of consumers [23], probably WOM can also influences decision on choosing another marketing channel. Based on Keaveney's [24] model of customers' service switching behavior one can identify some vital factors for switching marketing channel.…”
Section: Customer Journey In Buying Processmentioning
confidence: 99%